An investigation of the molecular genetics of some disorders of the mitochondrion - Poulton, J (1990)
Mitochondrial DNA is exclusively maternally inherited, and encodes a proportion of the subunits of the electron transport chain. As some of the mitochondrial myopathies show a maternal pattern of inheritance and/or a biochemical defect of respiratory chain components, they could be caused by mutations in the mitochondrial genome. Leber's hereditary optic neuropathy could arise in the same way, as it is maternally inherited. The main aim of this project was to determine whether mutations of mitochondrial DNA are responsible for these diseases. During the period of the study, rearrangements of mitochondrial DNA were described in mitochondrial myopathy (Holt et al. 1988b), Leber's hereditary optic neuropathy (Wallace et al. 1988a) and Pearson's syndrome. Restriction enzyme analysis of mitochondrial DNA from blood using five enzymes in 10 patients with mitochondrial myopathy did not reveal any major rearrangements in 83% of the protein coding regions. Similarly, the only point mutations in the 5% of this region which comprised the restriction sites were probably population polymorphisms. Ultimately 3/10 patients, all of whom had external ophthalmoplegia, were shown to have mitochondrial DNA deletions in muscle which were not readily detectable in blood. The polymerase chain reaction was then applied in order to detect abnormal mtDNAs which might be present in the blood of 24 patients, with a view to developing this method for noninvasive diagnosis. A product of appropriate size was obtained in 8. These observations confirmed that low levels of deleted mtDNAs are present in blood of a substantial proportion of patients, and in two asymptomatic relatives. Sequence analysis suggested that mitochondrial DNA deletions were present in the germline of this family. Two patients with direct tandem duplications of mitochondrial DNA and mitochondrial myopathy are described. The breakpoint regions between duplicated segments were amplified using the polymerase chain reaction, cloned and sequenced. The distribution of normal and abnormal genomes in different tissues was investigated using Southern hybridisation, and in different cells within the same tissue using PCR. In each case the gene for cytochrome 4 oxidase subunit I (MTCOXl) was interrupted, creating reading frames which if transcribed and translated would result in truncated versions of this peptide. Heteroplasmy and mosaicism for the abnormal mtDNA population was apparent. Nineteen patients with Leber's Hereditary Optic Neuropathy were investigated for the presence or absence of the point mutation described by Wallace et al. (1988a), using Southern hybridisation, and sequencing, oligonucleotide probing and competitive oligonucleotide priming of PCR products. In 14 cases the point mutation was confirmed, and 5 had the wildtype sequence in this region. Of the 5 patients with the normal sequence, only one had a clear family history of LHON. Sequence analysis in this patient revealed a single base insertion between bp 11, 718 and 11, 719 producing a frame shift. If transcribed and translated this would result in a truncated peptide. This provides evidence that Wallace's mutation is present in the majority of patients with LHON, and support for the view that both mutations are causative. These observation support the contention that mutations of mitochondrial DNA may cause disease. Further work may provide insights into the mechanism by which they cause the phenotype, and suggest therapeutic possibilities. The use of the polymerase chain reaction to detect deletions in blood may enable non-invasive diagnosis in up to 40% of patients with mitochondrial myopathy and identification of relatives at risk of transmitting the disease.